Promosi Perpustakaan dalam Minat Kunjung di Sekolah Dasar Negri 10 Minas - Trihandayani, Rani; Sudiar, Nining (CV. Publikasi Indonesia, 2022)
The presence of libraries in the school environment is basically a process of exchanging information between authors and library users. Various definitions of libraries are discussed in various sources, but the library is defined simply by some people as a place to store collections, especially in the form of prints. This type of research uses descriptive research methods. Descriptive research is a method for examining the current state of a group of people, objects, conditions, systems of thought, or classes of events. The purpose of such descriptive research is to provide a systematic, correct and accurate description, description or description of the nature of the relationship between the phenomena studied. The method used in this study is a qualitative research method. Qualitative method is a research method that aims to obtain a comprehensive understanding of the phenomena experienced by research subjects by describing in words and language, in the context of specific experiences and using various natural methods. One of the marketing activities for library services to students is by This promotion, of course, is a means used by librarians to introduce the library to broad students so that they know and are interested in coming and using the library because a library without visitors is of no use.